Production of Triticale Genotypes in Two Salt Affected Areas of Bangladesh for Grain and Fodder - Ali, M Yusuf; Zaman, SM; Amin, M; Amin, MR; Aktar, Shamima (The Agriculturists, 2011)
Fifteen genotypes of Triticale were tested in two salt affected locations namely Satkhira and Noakhali during 2006-07. At Satkhira, genotype E6 and E14 produced significantly the highest grain yield (2.00 t/ha) from December 28 sowing date. While the highest fodder yield was obtained from line E7 (6.94 t/ha). However, E6 produced good amount of green fodder (5.62 t/ha) as well as the highest grain yield (2.00 t/ha), so, genotype E6 could be used for dual purposes. On the other hand, at Noakhali genotype E5 gave the highest grain yield (2.48 t/ha) which was statistically similar to E11. However, E11 produced the highest amount of green fodder (9.88 t/ha). Hence, E11 could be used for the dual purposes. In both locations it was observed that soil salinity above 6-7 dS/m hampered the growth and development of the crop. To reduce the toxic effects of salinity on seeds, irrigation would be advisable just after sowing. Crop failure was observed when soil salinity was above 10 dS/m. Keywords: Triticale genotypes; salinity; grain; fodder. DOI: 10.3329/agric.v8i2.7570 The Agriculturists 8(2): 1-7(2010)